2000
DOI: 10.1046/j.1525-1489.2000.00247.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Transpyloric Enteral Nutrition in the Critically Ill Child

Abstract: To assess the use and complications of transpyloric enteral nutrition (TEN) in the critically ill child we evaluated prospectively all children who received TEN in a pediatric intensive care unit (PICU) of a tertiary university hospital. The type of nutrition used, its duration, medication administered, tolerance, gastrointestinal complications (vomiting, abdominal distension or excessive gastric residue, diarrhea, and pulmonary aspiration), nongastrointestinal complications, and mortality were assessed. A com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Enteral nutrition is safe and effective in most critically ill children [ 1 , 2 ]. The early initiation of enteral nutrition may preserve mechanical and immunological gut barrier function, stimulating intestinal trophism, and reducing bacterial translocation and the incidence of sepsis and multisystem failure [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enteral nutrition is safe and effective in most critically ill children [ 1 , 2 ]. The early initiation of enteral nutrition may preserve mechanical and immunological gut barrier function, stimulating intestinal trophism, and reducing bacterial translocation and the incidence of sepsis and multisystem failure [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous studies in the past decade have demonstrated that the majority of critically ill children tolerate enteral nutrition well [2,7,11,16,17,35]. Enteral nutrition is more physiological, has a trophic effect on the intestinal mucosa, and stimulates the intestinal immune system, decreasing bacterial overgrowth and translocation; it therefore reduces the incidence of sepsis and multiorgan failure.…”
Section: What Type Of Nutrition Should the Critically Ill Child Rementioning
confidence: 99%
“…Furthermore, enteral nutrition is associated with fewer hepatic and metabolic complications than parenteral nutrition, it is cheaper, it does not require special preparation, and it can be started and modified at any time. At the present time, although very few studies have compared the efficacy and complications of enteral and parenteral nutrition, and although enteral nutrition has not been shown to reduce mortality or length of PICU stay in comparison with parenteral nutrition, the majority of paediatric intensive care physicians consider that enteral nutrition should be the first method for feeding the critically ill child and that it should be started early [2,7,11,16,17,3537]. …”
Section: What Type Of Nutrition Should the Critically Ill Child Rementioning
confidence: 99%